2019
DOI: 10.1101/865840
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Vivo Emergence of a Novel Protease Inhibitor Resistance Signature in HIV-1 Matrix

Abstract: Background: Protease Inhibitors (PIs) are the second-and last-line therapy for the majority of HIV-infected patients worldwide. Only around 20% of individuals who fail PI regimens develop major resistance mutations in protease. We sought to explore the role of mutations in gag-protease genotypic and phenotypic changes within six Nigerian patients who failed PI-based regimens without known drug resistance associated protease mutations in order to identify novel determinants of PI resistance.Methods: Target enri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In the absence of major PI mutations, we first examined non-synonymous mutations across the whole genome (Figures 4-6), with a specific focus on pol (to identify known first and second line NRTI-associated mutations) and gag (given its known involvement in PI susceptibility). We and others have previously shown that gag mutations accumulate during non-suppressive PI therapy 34,35 .…”
Section: Changing Landscapes Of Non-synonymous and Synonymous Mutationsmentioning
confidence: 84%
“…In the absence of major PI mutations, we first examined non-synonymous mutations across the whole genome (Figures 4-6), with a specific focus on pol (to identify known first and second line NRTI-associated mutations) and gag (given its known involvement in PI susceptibility). We and others have previously shown that gag mutations accumulate during non-suppressive PI therapy 34,35 .…”
Section: Changing Landscapes Of Non-synonymous and Synonymous Mutationsmentioning
confidence: 84%
“…In a recent analysis of pooled evidence on virological and resistance outcomes following DTG failure in SSA region, there was an overall high rate of virological response to DTG; 88.5% (95% CI: 73.8-97.8) with the overall proportion of patients failing showing limited evidence of DRMS 19 over short periods of time. It is likely that prolonged virologic failure will select for DRM to components of ART regimens within the viral quasispecies as a result of intrahost evolution 20,21 .…”
Section: Discussionmentioning
confidence: 99%